Green leaf volatiles and jasmonic acid enhance susceptibility to anthracnose diseases caused by Colletotrichum graminicola in maize. (27th February 2020) - Gorman, Zachary; Christensen, Shawn A.; Yan, Yuanxin; He, Yongming; Borrego, Eli; Kolomiets, Michael V.
Abstract: Colletotrichum graminicola is a hemibiotrophic fungus that causes anthracnose leaf blight (ALB) and anthracnose stalk rot (ASR) in maize. Despite substantial economic losses caused by these diseases, the defence mechanisms against this pathogen remain poorly understood. Several hormones are suggested to aid in defence against C. graminicola, such as jasmonic acid (JA) and salicylic acid (SA), but supporting genetic evidence was not reported. Green leaf volatiles (GLVs) are a group of well‐characterized volatiles that induce JA biosynthesis in maize and are known to function in defence against necrotrophic pathogens. Information regarding the role of GLVs and JA in interactions with (hemi)biotrophic pathogens remains limited. To functionally elucidate GLVs and JA in defence against a hemibiotrophic pathogen, we tested GLV‐ and JA‐deficient mutants, lox10 and opr7 opr8, respectively, for resistance to ASR and ALB and profiled jasmonates and SA in their stalks and leaves throughout infection. Both mutants were resistant and generally displayed elevated levels of SA and low amounts of jasmonates, especially at early stages of infection. Pretreatment with GLVs restored susceptibility of lox10 mutants, but not opr7 opr8 mutants, which coincided with complete rescue of JA levels. Exogenous methyl jasmonate restored susceptibility in both mutants when applied before inoculation, whereas methyl salicylate did not induce further resistance in either of the mutants, but did induce mutant‐like resistance in the wild type. Collectively, this study reveals that GLVs and JA contribute to maize susceptibility to C. graminicola due to suppression of SA‐related defences. Abstract : Jasmonic acid and green leaf volatiles act as key susceptibility factors of maize to Colletotrichum graminicola by suppressing salicylic acid‐mediated defence during the biotrophic phase of growth.